Assessing time and financial costs of bus delays in the Ústí nad Labem Region, Czech Republic - Martin Scháno; Alexandra Dvořáčková; Ondřej Smíšek (Acta Polytechnica CTU Proceedings)
This publication focuses on the development of a regional system for monitoring and evaluating public bus delays in the Ústí nad Labem Region in the Czech Republic. The case study, through a questionnaire survey, addresses the issue of the value of time loss caused by delays in regional public bus transport in the Ústí nad Labem Region from both a societal and individual passenger perspective. The survey includes, in addition to opportunity costs, the necessity to use earlier buses due to uncertainty and the potential real financial loss of passengers, for instance, due to late arrival to work and p otential employer sanctions. Routes for the questionnaire survey were selected based on an analysis of the movement of the bus fleet to represent typical situations applicable to the entire bus transport network. The result is a financial evaluation of the losses caused by bus delays in relation to the number of passengers, the purpose of their journeys, and the value of their time. The findings reveal relatively high costs of time losses, which, when applying a co st benefit approach, allow for the return on larger infrastructure investments aimed at reducing these delays. The research results will contribute to the development of issues evaluating the economic efficiency of investments in transport infrastructure.